2015
DOI: 10.1016/j.jtbi.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and simulation of layer-specific mitral valve interstitial cells deformation under physiological loading

Abstract: Within each of the four layers of mitral valve (MV) leaflet tissues there resides a heterogeneous population of interstitial cells that maintain the structural integrity of the MV tissue via protein biosynthesis and enzymatic degradation. There is increasing evidence that tissue stress-induced MV interstitial cell (MVIC) deformations can have deleterious effects on their biosynthetic states that are potentially related to the reduction of tissue-level maintenance and to subsequent organ-level failure. To bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 87 publications
3
87
0
Order By: Relevance
“…In order to estimate changes in MVIC deformation throughout pregnancy, we performed FE simulations using ABAQUS (Dassault Systèmes Simulia Corp.) for a representative volume element (RVE) of valve leaflet tissue under biaxial tension, following established procedures [17]. Briefly, 10 MVICs were embedded in a 100 Â 100 mm 2 ECM region as Saint VenantKirchhoff ellipsoidal inclusions of approximately 5 kPa stiffness, with an initial NAR equal to the average found for NP specimens.…”
Section: Mitral Valve Interstitial Cell Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to estimate changes in MVIC deformation throughout pregnancy, we performed FE simulations using ABAQUS (Dassault Systèmes Simulia Corp.) for a representative volume element (RVE) of valve leaflet tissue under biaxial tension, following established procedures [17]. Briefly, 10 MVICs were embedded in a 100 Â 100 mm 2 ECM region as Saint VenantKirchhoff ellipsoidal inclusions of approximately 5 kPa stiffness, with an initial NAR equal to the average found for NP specimens.…”
Section: Mitral Valve Interstitial Cell Geometrymentioning
confidence: 99%
“…As the insertion of new fibrils causes the fibres to become longer and more undulated, recruitment stretch would steadily increase and normal MVIC geometry would be restored. In direct correlation with local collagen fibre density, it has been shown that MVIC deformation varies across the different tissue layers of the MV leaflet [17]. It is therefore not surprising that MV growth and remodelling is also layer-specific, as demonstrated by the non-uniform changes in layer thicknesses seen in pregnancy [13].…”
Section: Delayed Restoration Of Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tissue stressinduced MVIC deformation can have deleterious effects on the biosynthetic states of MVICs that are related to the reduction of tissue maintenance as well as the organ-level failure. Therefore, to better understand the interrelationships between tissue-level loading and cellular responses, we developed an integrated experimental-computational approach in a parallel study (60) to quantify the in situ layer-specific MVIC deformations under controlled biaxial tension loading, and to explore the interrelationship between the MVIC stiffness and deformation to layer-specific tissue mechanical and structural properties. We found that MVIC deformation is primarily controlled by each tissue layer's respective structure and mechanical behavior rather than the intrinsic MVIC stiffness.…”
Section: Relation To Cellular Deformation and Strain-induced Tissue Fmentioning
confidence: 99%
“…[6][7][8][9][10] The MV surface is covered with endothelial cells, which interact with VICs to maintain the integrity of valves and also regulate the leaflets' mechanical properties. 11 MV insufficiency leading to regurgitation affects >2% of the population and, most frequently, is caused by mitral valve prolapse (MVP). 12,13 MVP is mainly due to myxomatous degeneration, leading to altered mechanical stress and turbulent flow in the proximity to the MV leaflets.…”
Section: Introductionmentioning
confidence: 99%